The gut and heart’s role in reward processing - Minel Arinel; Karim Abdelaal (Frontiers in Integrative Neuroscience, 2025)
Reward processing, which ensures survival, has evolved to also shape emotions, learning, and overall well-being. While traditional models of reward have focused predominantly on central neural circuits, emerging evidence underscores the role of peripheral bodily signals. This represents a new opportunity by which we may understand neurological and neuropsychiatric health. In this review, we explore the gut-brain and heart-brain interfaces in reward processing, delineating their contributions across distinct phases of reward and offering insights into their bioenergetic significance. By framing this interplay within an adaptive and clinical context, we propose new avenues for understanding and treating neuropsychiatric disorders through a mind–body medicine lens.